Synthesis and characterization of magnetic cross-linked enzyme aggregate and its evaluation of the alternating magnetic field (AMF) effects in the catalytic activity - Lucena, Guilherme N. [UNESP]; Santos, Caio C. dos [UNESP]; Pinto, Gabriel C. [UNESP]; Piazza, Rodolfo D. [UNESP]; Guedes, Wesley N. [UNESP]; Jafelicci Júnior, Miguel [UNESP]; de Paula, Ariela V. [UNESP]; Marques, Rodrigo Fernando C. [UNESP] (Elsevier, 2020)
A magnetic cross-linked enzyme aggregate (MCLEA) of cellulases and a non-magnetic analogue (CLEA) were synthesized and further investigated. The obtained MCLEA and CLEA showed a high enzyme loading efficiency of 90% and 88%, respectively. However, the MCLEA presented an activity 33% higher than the CLEA one, suggesting a catalytic enhancement effect as a result of magnetic nanoparticle presence in cross-linked cellulase aggregates structure. In addition, MCLEA shows an unusual behavior with highest enzymatic activity at low temperatures near to 37 °C. Lastly, a full factorial design (2x2) with two variables at two levels, frequency (203–420 kHz) and amplitude (3–6 kA m−1), was used in order to better investigate the effects of an alternating magnetic field (AMF) on MCLEA activity. AMF application decreased MCLEA activity, particularly in the highest values of frequency and amplitude, when compared to condition field free. In addition, frequency implied in more significant effects on MCLEA activity when compared to AMF amplitude.
Keywords: Alternating magnetic field; Enzyme immobilization; Magnetic nanoparticles; Magnetic supports